Deductive an inductive approaches to teaching grammar: attitudes of grade 9 EFL teachers in the Mekong Delta : - Nguyễn, Lâm Trúc Đào (Trường Đại học Cần Thơ, 2020)
This study was conducted to investigate grade 9 EFL teachers’ attitudes toward deductive and inductive approaches to teaching grammar in the Mekong Delta. Furthermore, which grammar points in grade 9 English textbook could be taught better with deductive or inductive approaches to teaching grammar were displayed. The results showed that all grade 9 EFL teachers had positive attitudes towards deductive and inductive approaches to teaching grammar, Moreover, the majority of grade 9 EFL teachers preferred utilizing inductive and integrated approaches to teach grammar. In addition, all grammar points in the grade 9 English textbook were taught with both inductive and deductive approaches to teaching grammar.